Perlindungan Hukum Terhadap Konsumen Kosmetik Pemutih Wajah “Cream HN” Dalam Transaksi Jual Beli Online Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Wahyuni, Sri; Rahmatiar, Yuniar; Abas, Muhamad (Wajah Hukum, 2023)
Cosmetics are used primarily for women for various purposes such as to make an attractive appearance. One of them is the HN Cream product, which is still a serious problem, which includes products that are not as safe as consumer expectations. As a result of using these products, it causes financial losses and also skin diseases including skin peeling, acne breakouts, and others. This is not in accordance with Law no. 8 of 1999 regarding Consumer Protection. The main problem that the author raises in this study is how the process of applying legal protection to consumers of facial whitening cosmetics Cream HN in online buying and selling transactions according to Law no. 8 of 1999 concerning Consumer Protection and how are the factors inhibiting the implementation of consumer protection for Cream HN cosmetics in online buying and selling transactions. His method applies an empirical juridical approach, and is carried out directly to the place that is the object of his research. Researchers also obtained data through the interview process. His research was obtained from the results of selling Cream HN online. The approach uses a primary approach, which is in the form of data obtained from field studies. The result is that to provide legal protection guarantees regarding consumers, business actors when selling online must be based on Law no. 8 of 1999 regarding consumer protection.